Synthesis of Silver Nanoparticles Using Triticum aestivum and Its Effect on Peroxide Catalytic Activity and Toxicology - Shobha Waghmode; Pooja Chavan; Vidya Kalyankar; Sharada Dagade (Journal of Chemistry)
The synthesis of stable silver nanoparticles using bioreduction method was investigated. Biological synthesis of silver nanoparticles using Triticum aestivum (khapali ghahu) extract was investigated. The effect of a specific variety of plants and how it affects the growth of silver nanoparticles was investigated in our work and it was polydispersed. UV-visible spectroscopy was used to monitor the formation of silver nanoparticles within 15 minutes. The peaks in XRD pattern are in good agreement with those of face-centered-cubic form of metallic silver. Further the IR and TEM shows confirmation of nanocrystalline nature of silver nanoparticles. These nanoparticles dislodged by ultrasonication showed an absorption peak at 430 nm in UV-visible spectrum corresponding to the Plasmon resonance of silver nanoparticles. UV-visible titration experiments showed evidence that silver nanoparticles facilitate hydrogen peroxide reduction showing excellent catalytic activity at 200 μL. In this preliminary toxicology study, Earthworm toxicology we checked and is stable up to 1500 ppm concentration. The use of plant extract for silver nanoparticles synthesis offers the benefits of eco-friendliness and amenability for large-scale production.